The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2011
DOI: 10.1590/s1413-81232011000700077
|View full text |Cite
|
Sign up to set email alerts
|

Construção da integralidade no cuidar de pessoas com diabetes mellitus em um centro de saúde em Feira de Santana (BA)

Abstract: This study analyses the care of people with diabetes mellitus (DM), under the light of integrality, through access, bond-accountability, and team formation in a healthcare unit of Feira de Santana, Bahia State. It is a qualitative study adopting a critical and reflexive approach. The subjects were healthcare workers (Group I) and users registered in the diabetes program (Group 2). Data collection techniques included a structured interview and systematic observations, while the data analysis was based on conten… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
1
0
9

Year Published

2013
2013
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(10 citation statements)
references
References 13 publications
0
1
0
9
Order By: Relevance
“…Even with the support and integration built between the researcher and the participants through the dialogues, it was found that vertical educational practices are still frequent in the municipality where the study took place. The care provided to people with diabetes is still based on the model centered on the health professional, in which there is no bonding, there is no welcoming and humanization in the care provided to patients, which does not allow the comprehensiveness recommended for the patient to be the protagonist of the process 39 .…”
Section: Final Considerationsmentioning
confidence: 99%
“…Even with the support and integration built between the researcher and the participants through the dialogues, it was found that vertical educational practices are still frequent in the municipality where the study took place. The care provided to people with diabetes is still based on the model centered on the health professional, in which there is no bonding, there is no welcoming and humanization in the care provided to patients, which does not allow the comprehensiveness recommended for the patient to be the protagonist of the process 39 .…”
Section: Final Considerationsmentioning
confidence: 99%
“…Logo, constata-se que estes achados são divergentes dos resultados de estudo em que, ao investigar sobre integralidade no processo de cuidar de pessoas com diabetes mellitus (DM), percebeu-se que estes usuários esperam longo tempo pelo atendimento, na maioria das vezes de pé no corredor, encostados em paredes, perto dos consultórios ou formando aglomeração em frente às portas (25) . De fato, essa realidade comunga com a proposta de Humanização (4,12) , concebida pelo Ministério da Saúde no ano de 2004, a qual objetiva, entre outras coisas, valorizar o respeito aos usuários, melhorando a infraestrutura dos serviços, respeitando a privacidade e promovendo a ambiência acolhedora e confortável.…”
Section: () Os Pacientes Eles Não Voltam Pra Casa Sem O Atendimento Não De Jeito Nenhum (Aux1)unclassified
“…O CSF encontrava-se numa situação ruim de acesso ao atendimento antes da formação dos grupos nas comunidades. Sendo assim, o atendimento era organizado sem processos de acolhimento, de modo burocrático a partir de filas, por ordem de chegada, as quais privilegiavam não aqueles que necessitavam de assistência urgente, mas os que se mostravam mais resistentes (13,25) :…”
Section: () Os Pacientes Eles Não Voltam Pra Casa Sem O Atendimento Não De Jeito Nenhum (Aux1)unclassified
“…O PAMG enquanto serviço vinculado à ABS está sujeito aos entraves operacionais desta última, tais como o acesso deficitário dos usuários aos serviços, a automatização do trabalho em saúde sob a lógica da produtividade e a participação inexpressiva dos usuários no processo de decisão clínica e no planejamento em saúde 16 . Esses entraves comprometem, assim, a prática assistencial autorreflexiva e a compreensão das necessidades de saúde dos portadores de DM 13,14,16 .…”
Section: Introductionunclassified